Novel metasurface substrate material-based metasurface broadband wave-absorbing composite material and preparation method thereof
By using aramid unidirectional cloth as the substrate for the FSS pattern and designing a dielectric protective layer on the pattern surface layer, the problems of instretchability and poor compatibility of the FSS substrate in the prior art are solved, and the efficient wave absorption and good mechanical properties of the wave-absorbing composite material are achieved.
Patent Information
- Application Number
- CN202411735893.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing FSS substrate is not stretchable and cannot be applied to complex three-dimensional structures; the PI film, as a metamaterial substrate, has poor compatibility with resin, resulting in a decrease in mechanical and absorbing properties of composite materials; the woven fabric surface is rough, and the FSS pattern is highly uneven, affecting the absorbing properties; the FSS pattern is susceptible to wear and partial layers on the outer surface of the structure, resulting in a decrease in absorbing properties.
Aramid unidirectional cloth is used as the substrate for the FSS pattern, and an FSS pattern is prepared by screen printing, and a dielectric protective layer is designed on the surface of the pattern. Combined with metamaterial electromagnetic simulation design, the goal of "thin, light, wide and strong" of wave absorbing composite materials is achieved.
The preparation integrity and square resistance uniformity of the FSS pattern are improved, the absorption efficiency and mechanical properties of the wave absorbing composite material are enhanced, and the absorption performance of the pattern is reduced due to wear and partial layers is avoided.
Smart Images

Figure CN119581872A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of absorbing materials, and in particular relates to a super-surface broadband absorbing composite material based on a novel super-surface substrate material and a preparation method thereof. Background Art
[0002] With the development of information technology and science and technology, electromagnetic stealth and electromagnetic protection have been more and more widely used in various fields. In the military field, the improvement of stealth performance can enhance the depth strike capability and breakthrough power of weapons, and can gain the upper hand in modern warfare and easily break the offensive and defensive pattern. Therefore, the stealth of military targets such as aircraft, missiles, ships and radars has always been a research hotspot in various countries. In the civilian field, with the development of social informatization, the demand for mobile data has exploded, and mobile communication systems have also rapidly iterated, and more and more frequency bands are used to achieve wireless communication. Information systems are rapidly developing towards multi-function, high performance and high reliability. In order to improve system security and reliability and reduce the electromagnetic radiation of equipment, electromagnetic protection of equipment is required in many occasions.
[0003] The engineering application of absorbing materials in the field of aviation requires them to have characteristics such as light weight, high temperature resistance, corrosion resistance, etc., and also has certain requirements for mechanical properties. Therefore, absorbing materials with integrated structural and functional design are one of the key technologies to solve their practical engineering applications. The performance of metamaterial absorbing structures can be adjusted by designing the size and resistance of the two-dimensional plane pattern. The application of metamaterials in the design of absorbing structures can minimize the impact on the structural bearing function while maintaining the absorbing performance. Making the designed metamaterials and integrating them into aviation components to achieve specific functions are also key technical issues for metamaterials to truly achieve engineering applications from the laboratory. Frequency selective surface (FSS) is a single-layer or multi-layer planar structure composed of a large number of identical units arranged in a two-dimensional periodic manner. The pattern structure and arrangement of the periodic units, the thickness and material of the dielectric and absorbing materials, the polarization and oblique incidence of the incident wave, and other factors determine the performance of the frequency selective surface. Sheet resistance, referred to as square resistance, refers to the resistance from edge to edge of a square thin film conductive material. The size of the sheet resistance is independent of the sample size, and its unit is Ω / sq. The resistance value of the FSS patch square resistor will affect the peak position, depth and width of the resonant absorption peak of the absorbing material.
[0004] In most studies, FSS is realized on non-stretchable substrates. Considering the manufacturing process of composite materials, it is difficult to apply these methods to complex three-dimensional structures. Therefore, in recent years, some studies have used polyimide (PI) films or fiber fabrics as substrate materials to prepare FSS patterns. However, PI films have poor compatibility with resins when used as metamaterial substrates in the preparation of composite materials. This compatibility problem will lead to a decrease in the mechanical properties and wave absorption performance of the composite material. Most fabrics have a rough surface, and due to the interweaving of warp and weft yarns, the height of the FSS pattern is uneven, resulting in a random distribution of the square resistance of the prepared FSS pattern, which will seriously affect the wave absorption performance of the final composite material.
[0005] The surface flatness of aramid unidirectional fabric is high, which helps to improve the accuracy and quality of the pattern in the FSS pattern preparation process and reduce the problems of pattern diffusion and surface unevenness. Figure 1 As shown in the figure, when the FSS pattern is printed on the surface of aramid plain fabric, due to the influence of the fiber capillary effect, the conductive ink diffuses, and the interweaving of the warp and weft yarns makes the thickness of the prepared pattern uneven, resulting in large differences in the FSS pattern. Figure 1 (a1) is a real picture of FSS pattern printed on aramid plain fabric, a2 is a schematic diagram of ink diffusion, and a3 is a schematic diagram of ink thickness. Figure 1 (b) is a physical picture of the FSS pattern printed on aramid unidirectional cloth. Secondly, aramid unidirectional cloth generally has higher strength and modulus than woven fabrics due to the directional arrangement of its fibers, which enables the aramid unidirectional cloth to better maintain the integrity and accuracy of the pattern when subjected to mechanical stress. Furthermore, compared with PI film, aramid unidirectional cloth has higher compatibility with resin. The present invention uses aramid unidirectional cloth as the printing substrate for the FSS pattern, and the prepared absorbing composite material has superior absorbing performance and mechanical properties compared with existing studies. Finally, we designed a dielectric protective layer on the surface of the FSS pattern to solve the problem that in actual applications, when the FSS pattern is exposed on the outer surface of the structure and is subjected to external force loading, wear damage and local stratification lead to a decrease in the absorbing performance of the absorber. Finally, a structurally functional integrated absorbing composite material with mechanical bearing and broadband absorbing performance is realized. Summary of the invention
[0006] The problems existing in the prior art include the problem that the existing FSS substrate is not stretchable and cannot be applied to complex three-dimensional structures, the problem that the existing research uses PI film as the FSS substrate but has poor compatibility with the resin matrix, the problem that the existing research uses woven fabric as the FSS substrate and the integrity and uniformity of the prepared pattern are reduced, and the existing FSS pattern on the outer surface of the structure suffers from wear damage and local stratification under various loading conditions in actual applications, resulting in a reduction in the absorbing performance of the absorber.
[0007] The present invention provides a method for preparing a super-surface broadband wave-absorbing composite material based on a novel super-surface substrate material, comprising the following steps:
[0008] S1: adding polymer beads to a PEDOT:PSS dispersion, standing, stirring, removing the beads, freeze-drying to obtain solid PEDOT:PSS, and mixing the solid PEDOT:PSS with a solvent to obtain a PEDOT:PSS conductive ink;
[0009] S2: The aramid unidirectional fabric is vibrated and cleaned in acetone and dried; the PEDOT:PSS conductive ink obtained in S1 is used to prepare an FSS pattern on the treated aramid unidirectional fabric by screen printing, and then placed in an oven for drying to obtain an aramid unidirectional fabric printed with the FSS pattern;
[0010] S3: Apply a release agent to the mold surface, cut the aramid fiber unidirectional / epoxy resin prepreg, aramid unidirectional cloth, aramid unidirectional cloth printed with FSS pattern, epoxy resin film and carbon fiber unidirectional / epoxy resin prepreg into the size of the mold, lay the carbon fiber unidirectional / epoxy resin prepreg, aramid fiber unidirectional / epoxy resin prepreg, epoxy resin film, aramid fiber unidirectional cloth printed with FSS pattern and epoxy film from bottom to top, perform hot pressing molding, naturally cool and demold, and obtain a metasurface broadband absorbing composite based on the new metasurface substrate material.
[0011] Furthermore, the standing time described in S1 is 1 to 2 hours, the stirring interval time is 20 to 30 minutes, and the freeze-drying time is 72 hours.
[0012] Furthermore, the shaking cleaning time in S2 is 2 to 5 hours, the drying temperature is 80 to 100° C., and the time is 0.5 to 1 hour.
[0013] Furthermore, the carbon fiber unidirectional / epoxy resin prepreg described in S3 is 1 to 3 layers.
[0014] Furthermore, the size of the mold in S3 is 200 mm×200 mm.
[0015] Furthermore, the hot pressing process described in S3 is performed at a temperature of 150° C., a pressure of 8 MPa, and a time of 25 min.
[0016] A supersurface broadband absorbing composite material based on a novel supersurface substrate material, wherein the supersurface broadband absorbing composite material based on the novel supersurface substrate material is a layered structure in which two layers of carbon fiber unidirectional / epoxy resin prepreg are laid in a horizontal and vertical cross-laying manner on the lower layer, six layers of aramid fiber unidirectional / epoxy resin prepreg are laid in the middle layer, and a layer of epoxy film, a layer of aramid fiber unidirectional cloth printed with an FSS pattern, and a layer of epoxy film are laid in sequence on the uppermost layer from bottom to top.
[0017] Beneficial Effects
[0018] By providing a method for preparing a metasurface broadband absorbing composite material based on a novel metasurface substrate material, the metasurface pattern is completely prepared by using aramid unidirectional cloth as the substrate of the FSS pattern, and the uniformity of the square resistance of the metasurface pattern is regulated. Combined with the electromagnetic simulation of the metamaterial, the goal of "thin, light, wide and strong" absorbing performance of the absorbing composite material is achieved, and the absorbing performance shows better reliability and durability in various application environments.
[0019] Through the preparation method of a supersurface broadband absorbing composite material based on a new supersurface substrate material provided by the present invention, a dielectric protection layer is designed on the surface of the FSS pattern to solve the problem that in practical applications, when the FSS pattern is exposed on the outer surface of the structure and is subjected to external force loading, wear damage and local stratification lead to a decrease in the absorbing performance of the absorber. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0021] In the figure:
[0022] Figure 1 The actual pictures of FSS patterns printed on different aramid substrates and the schematic diagram of ink diffusion;
[0023] Figure 2 It is the electromagnetic parameter diagram of the aramid fiber / epoxy resin composite material of the present invention;
[0024] Figure 3 The top view and side view of the wave absorbing body containing square ring unit geometric pattern of the present invention;
[0025] Figure 4 A schematic diagram of the FSS periodic structure verified by the experiment of the present invention;
[0026] Figure 5It is a schematic diagram of the ply structure of Comparative Example 1 of the present invention;
[0027] Figure 6 This is a schematic diagram of the ply structure of Comparative Example 2 of the present invention;
[0028] Figure 7 Schematic diagram of the ply structure of Comparative Example 3 of the present invention;
[0029] Figure 8 It is a schematic diagram of the ply structure of Comparative Example 4 of the present invention;
[0030] Fig. 9 It is a schematic diagram of the ply structure of Comparative Example 5 of the present invention;
[0031] Fig.10 It is a schematic diagram of the ply structure of Comparative Example 6 of the present invention;
[0032] Fig.11 This is a schematic diagram of the ply structure of Example 1 of the present invention;
[0033] Fig.12 It is a schematic diagram of the ply structure of Comparative Example 7 of the present invention;
[0034] Fig.13 The surface and cross-sectional views of the structural and functional integrated wave-absorbing composite material of the present invention;
[0035] Fig.14 This is a test curve diagram of the wave absorption performance of Example 1 of the present invention;
[0036] Fig.15 The top view and side view of the wave absorbing body with square unit geometric pattern of the present invention;
[0037] Fig.16 It is a schematic diagram of the FSS periodic structure of the present invention;
[0038] Fig.17 It is a schematic diagram of the ply structure of Comparative Example 8 of the present invention;
[0039] Fig.18 It is a schematic diagram of the ply structure of Comparative Example 9 of the present invention;
[0040] Fig.19 It is a schematic diagram of the ply structure of comparative example 10 of the present invention. DETAILED DESCRIPTION
[0041] The following is a combination of Example 1 of the present invention and Comparative Examples 1 to 10 and the attached Figures 1 to 19, the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The present invention provides a method for preparing a super-surface broadband wave-absorbing composite material based on a novel super-surface substrate material, comprising the following steps:
[0043] S1: First, weigh the PEDOT:PSS dispersion, add the highly absorbent polymer beads thereto, let it stand at room temperature, stir occasionally, then remove the beads and put it in a refrigerator for pre-freezing; freeze-dry in a freeze dryer to obtain solid PEDOT:PSS; weigh the solid PEDOT:PSS, DMSO and deionized water, and manually mix them by pushing back and forth with two needles to make the PEDOT:PSS and the solvent completely mixed, thereby preparing the PEDOT:PSS conductive ink;
[0044] S2: The aramid unidirectional fabric is placed in an acetone solution in an ultrasonic cleaner for oscillation cleaning, and then placed in an oven for drying and standby use, to ensure that impurities and colloids on the fiber surface are completely removed; the desired FSS pattern is prepared on the treated aramid unidirectional fabric using PEDOT:PSS conductive ink by screen printing, and the fabric is placed in an oven to obtain an aramid unidirectional fabric printed with the FSS pattern;
[0045] S3: Use aramid fiber unidirectional / epoxy resin prepreg, aramid unidirectional cloth and epoxy resin film as dielectric layer, and carbon fiber unidirectional / epoxy resin prepreg as reflective layer; first apply release agent on the mold surface, and then cut aramid fiber unidirectional / epoxy resin prepreg, aramid unidirectional cloth, aramid unidirectional cloth printed with FSS pattern, epoxy resin film and carbon fiber unidirectional / epoxy resin prepreg into the size of the mold; lay several layers of carbon fiber unidirectional / epoxy resin prepreg on the bottom layer, lay several layers of aramid fiber unidirectional / epoxy resin prepreg on the middle layer according to thickness requirements, and lay a layer of epoxy film, a layer of aramid unidirectional cloth printed with FSS pattern and a layer of epoxy film on the top layer from bottom to top, and put them into the mold after being leveled. The unidirectional prepreg layers are laid in a horizontal and vertical cross manner to prevent deformation caused by excessive stress concentration during the hot pressing process. The mold is placed in a hot press, prepared by a hot pressing process, and demolded after natural cooling to obtain a super-surface broadband absorbing composite material based on a new super-surface substrate material. The composite material in the absorbing composite material refers to a composite material.
[0046] Example 1
[0047] S1: Weigh 100 mL of PEDOT:PSS (PHV500) dispersion, add 2 g of highly absorbent polymer beads, let stand at room temperature for 1 h, stir occasionally, and then remove the beads; put in a refrigerator for pre-freezing for 3 h, freeze-dry in a freeze dryer for 72 h to obtain solid PEDOT:PSS; take 1.5 g of solid PEDOT:PSS, 2 ml of DMSO and 18 ml of deionized water, and manually mix by manually operating two needles to push back and forth for more than 5 min to completely mix PEDOT:PSS and the solvent to prepare PEDOT:PSS conductive ink;
[0048] S2: The aramid fiber unidirectional fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities and colloids on the surface of the aramid fiber unidirectional fabric are completely removed; the desired FSS pattern is prepared on the treated aramid fiber unidirectional fabric using PEDOT:PSS conductive ink by screen printing;
[0049] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of aramid fiber unidirectional / epoxy resin prepreg on the middle layer, and lay a layer of epoxy film, a layer of aramid fiber unidirectional cloth printed with FSS pattern and a layer of epoxy film on the top layer from bottom to top. Put it into the mold after leveling. The layup diagram is shown as follows: Fig.11 As shown; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressurized, and finally cooled. It is hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0050] In S1, the volume ratio of DMSO should not exceed 50% of the total volume, and the viscosity of the conductive ink prepared by controlling the solid content of PEDOT:PSS at 5% to 9% is more suitable; the ratio of solid PEDOT:PSS to DMSO and deionized water can be adjusted within a certain range according to the square resistance of the required FSS pattern.
[0051] In S3, 1-3 layers of carbon fiber unidirectional / epoxy resin prepreg in the reflective layer are sufficient to achieve the full reflection effect of electromagnetic waves; the aramid fiber unidirectional / epoxy resin prepreg in the middle layer can also be replaced by aramid unidirectional cloth and epoxy resin film by alternating layers. There are no strict requirements for the surface density of aramid fiber unidirectional / epoxy resin prepreg, carbon fiber unidirectional / epoxy resin prepreg, aramid unidirectional cloth and epoxy resin film, but the epoxy resin used in the two prepregs and epoxy resin film should be the same, which is beneficial to the overall mechanical properties of the absorbing composite material. The hot pressing process parameters should be determined according to the selected epoxy resin prepreg. The hot pressing temperature should not exceed 200℃, otherwise it may have a negative impact on the conductivity of the PEDOT:PSS film. The hot pressing pressure should not exceed 15MPa, otherwise it is easy to produce extrusion deformation during processing, thereby destroying the integrity of the metasurface pattern. The demolding temperature should not be higher than 60℃, otherwise it will affect the overall mechanical properties of the absorbing composite material.
[0052] For the extraction of electromagnetic parameters of dielectric layer composite materials, a surface density of 700g / m 2 Aramid fiber plain weave / epoxy resin prepreg, wherein the aramid plain weave fabric surface density is 410g / m 2 Through the lamination and hot pressing process (hot pressing at 150℃, 8MPa for 25min, naturally cooling to below 50℃ and demolding), an aramid fiber / epoxy resin composite material with a thickness of 5.35mm was prepared, and then the waveguide size corresponding to each band within 2 to 18GHz was cut out by a cutting machine. Finally, the dielectric properties of the aramid / epoxy resin composite material were measured by the waveguide method, and the corresponding electromagnetic parameters were extracted. The specific test results are as follows Figure 2 shown. Figure 2 It includes the real part (ε') and imaginary part (ε") of the dielectric constant, the real part (μ') and imaginary part (μ") of the magnetic permeability.
[0053] For the measurement of the absorbing performance data, the square ring patch used in this patent has a strong design, including five parameters: the periodic unit side length P, the square ring outer side length a, the square ring inner side length b, the square ring patch square resistance cond and the dielectric layer thickness h. The top view and side view of the absorber with unit geometry are shown in the figure below. Figure 3 The designed metamaterial absorber is simulated using the frequency domain solver of the electromagnetic simulation software CST Microwave Studio. The absorber is placed in the xy plane in a periodic distribution, and the z direction is set as an open (add space) boundary. The simulation frequency is 2 to 18 GHz.
[0054] In order to verify the accuracy of the model, a composite material containing FSS film with the corresponding parameters of the optimal absorbing performance was prepared, with the periodic unit side length P = 8mm, the patch side length a = 6mm, b = 4mm, the patch square resistance cond = 30Ω / sq, and the dielectric layer thickness h = 3mm. The accuracy of the simulation was verified by comparing the experiment with the simulation. The square resistance of the FSS film was tested by the four-probe method, and the absorbing performance of the structural and functional integrated absorbing composite material containing the FSS film was tested by the bow method. Figure 4 shown.
[0055] In the test results of Example 1, the density of the absorbing composite material is 1.138 g / cm 3 , thickness 3.2mm, FSS film square resistance cond = 30 ± 8Ω / sq, reflection loss less than -10dB in the frequency range of 2 to 18GHz, effective absorption bandwidth (EAB) is 10.52GHz (7.28 to 17.80GHz), and tensile strength is 572.6MPa.
[0056] Fig.13 The microscopic morphology of the surface and side of the structure-function integrated wave-absorbing composite material of Example 1 is shown in FIG. Fig.13 (a) It can be seen that the surface of the aramid fiber / epoxy resin prepreg composite material is smooth after hot pressing and curing, and the epoxy resin has good coverage on the aramid fiber. Fig.13 (b) It can be seen that the interface performance of carbon fiber unidirectional / epoxy resin prepreg and aramid fiber / epoxy resin prepreg is good after hot pressing curing, and no obvious delamination phenomenon occurs.
[0057] Fig.14 The test results of the absorbing performance of the absorbing composite material of Example 1 show that the prepared metamaterial-based structural and functional integrated composite material achieves a reflection loss of less than -10dB in the frequency range of 7.28 to 17.80GHz, and the EAB is as high as 10.52GHz.
[0058] Comparative Example 1
[0059] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0060] S2: The PI film is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities on the surface of the PI film are completely removed; the desired FSS pattern is prepared on the treated PI film using PEDOT:PSS conductive ink by screen printing;
[0061] S3: Apply release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of aramid fiber unidirectional / epoxy resin prepreg on the middle layer, and lay a layer of epoxy resin film and a layer of PI film printed with FSS pattern on the top layer from bottom to top. The schematic diagram of the layering is shown in the figure. Figure 5 As shown, after being leveled, it is placed in a mold; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressed, and finally cooled, hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out, to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0062] In comparative example 1, the FSS pattern substrate is PI film + aramid fiber unidirectional / epoxy resin prepreg, and the top layer has no epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.008g / cm 3 , thickness 3.2mm, FSS film square resistance cond=30±5Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2~18GHz is 10.13GHz (7.28~17.41GHz), and tensile strength is 521.5MPa. However, since there is no protective layer on the upper layer of the FSS film, the film will fall off if placed in the outdoor environment for a long time, and the compatibility between the PI film and the epoxy resin is poor, and stratification occurs between the two, which leads to the collapse of the overall structure of the absorbing composite material and a sharp decline in the absorbing performance.
[0063] Comparative Example 2
[0064] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0065] S2: The PI film is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities on the surface of the PI film are completely removed; the desired FSS pattern is prepared on the treated PI film using PEDOT:PSS conductive ink by screen printing;
[0066] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of aramid fiber unidirectional / epoxy resin prepreg on the middle layer, and lay a layer of epoxy film, a layer of PI film printed with FSS pattern and a layer of epoxy resin film on the top layer from bottom to top. The layup diagram is shown in the figure. Figure 6As shown, after being leveled, it is placed in a mold; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressed, and finally cooled; hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out, to obtain a super-surface broadband absorbing composite material based on a new super-surface substrate material.
[0067] In comparative example 2, the FSS pattern substrate is a PI film, the dielectric layer is a unidirectional aramid fiber / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.098g / cm 3 , thickness 3.2mm, FSS film square resistance cond=30±5Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2~18GHz is 10.07GHz (7.06~17.13GHz), and tensile strength is 510.8MPa. However, due to the poor compatibility between PI film and epoxy resin, stratification occurs between the two, resulting in the collapse of the overall structure of the absorbing composite material and a sharp decline in the absorbing performance.
[0068] Comparative Example 3
[0069] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0070] S2: The PI film is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities on the surface of the PI film are completely removed; the desired FSS pattern is prepared on the treated PI film using PEDOT:PSS conductive ink by screen printing;
[0071] S3: Apply release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of aramid fiber plain weave / epoxy resin prepreg on the middle layer, and lay a layer of epoxy resin film, a layer of PI film printed with FSS pattern and a layer of epoxy resin film on the top layer from bottom to top. The layup diagram is shown in the figure. Figure 7 As shown, after being leveled, it is placed in a mold; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressed, and finally cooled; hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out, to obtain a super-surface broadband absorbing composite material based on a new super-surface substrate material.
[0072] In comparative example 3, the FSS pattern substrate is a PI film, the dielectric layer is an aramid fiber plain weave / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.102g / cm 3, thickness 3.2mm, FSS film square resistance cond = 30 ± 5Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2 to 18GHz is 9.45GHz (7.68 to 17.13GHz), and tensile strength is 432.7MPa. However, due to the poor compatibility between PI film and epoxy resin, stratification occurs between the two, resulting in the collapse of the overall structure of the later absorbing composite material and a sharp decline in absorbing performance. Secondly, because the surface of the aramid fiber plain fabric is not flat enough, the surface of the PI film printed with the FSS pattern after hot pressing is printed with fabric texture, which affects the accuracy of the FSS pattern and causes a slight decline in absorbing performance.
[0073] Comparative Example 4
[0074] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0075] S2: The glass fiber plain fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, ensuring that impurities and colloids on the surface of the glass fiber plain fabric are completely removed; the desired FSS pattern is prepared on the treated glass fiber plain fabric using PEDOT:PSS conductive ink by screen printing;
[0076] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of glass fiber plain weave / epoxy resin prepreg on the middle layer, and lay a layer of epoxy film, a layer of glass fiber plain weave fabric printed with FSS pattern and a layer of epoxy film on the top layer from bottom to top. The layup diagram is shown in the figure. Figure 8 As shown, after being leveled, it is placed in a mold; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressed, and finally cooled; hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out, to obtain a super-surface broadband absorbing composite material based on a new super-surface substrate material.
[0077] In comparative example 4, the FSS pattern substrate is glass fiber plain weave fabric, the dielectric layer is glass fiber plain weave / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.733g / cm 3, thickness 3.2mm, FSS film square resistance cond=30±40Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2~18GHz is 7.26GHz (10.06~17.32GHz), and tensile strength is 325.0MPa. Due to the capillary effect of glass fiber, the conductive ink diffuses, and the interweaving of warp and weft yarns makes the thickness of the prepared pattern uneven, resulting in large differences in FSS patterns, and the final pattern square resistance uniformity is poor, resulting in a decrease in absorbing performance.
[0078] Comparative Example 5
[0079] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0080] S2: The glass fiber unidirectional cloth is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities and colloids on the surface of the glass fiber unidirectional cloth are completely removed; the desired FSS pattern is prepared on the treated glass fiber unidirectional cloth using PEDOT:PSS conductive ink by screen printing;
[0081] S3: Apply release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of glass fiber unidirectional / epoxy resin prepreg in the middle layer, and lay a layer of epoxy film, a layer of glass fiber unidirectional cloth printed with FSS pattern and a layer of epoxy film on the top layer from bottom to top. The layup diagram is shown in the figure. Fig. 9 As shown; put it into the mold after leveling; place the mold in a hot press, evacuate, heat and pressurize, keep warm and pressurize, and finally cool it; hot press it at 150°C and 8MPa for 25min, cool it naturally to below 50°C, demold it and take it out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0082] In comparative example 5, the FSS pattern substrate is glass fiber unidirectional cloth, the dielectric layer is glass fiber unidirectional / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.825g / cm 3 , thickness 3.2mm, FSS film square resistance cond = 30 ± 8Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2 to 18GHz is 9.94GHz (8.06 to 18.00GHz), and tensile strength is 380.6MPa.
[0083] Comparative Example 6
[0084] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0085] S2: The aramid fiber plain fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities and colloids on the surface of the aramid fiber plain fabric are completely removed; the desired FSS pattern is prepared on the treated aramid fiber plain fabric using PEDOT:PSS conductive ink by screen printing;
[0086] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 6 layers of aramid fiber plain weave / epoxy resin prepreg on the middle layer, and lay a layer of epoxy film, a layer of aramid fiber plain weave fabric printed with FSS pattern and a layer of epoxy film on the top layer from bottom to top. The layup diagram is shown in the figure. Fig.10 As shown; put it into the mold after leveling; place the mold in a hot press, evacuate, heat and pressurize, keep warm and pressurize, and finally cool it; hot press it at 150°C and 8MPa for 25min, cool it naturally to below 50°C, demold it and take it out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0087] In comparative example 6, the FSS pattern substrate is aramid fiber plain weave fabric, the dielectric layer is aramid fiber plain weave / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.182g / cm 3 , thickness 3.2mm, FSS film square resistance cond=30±40Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2~18GHz is 6.68GHz (9.24~15.92GHz), and tensile strength is 455.3MPa. Due to the capillary effect of aramid fiber, the conductive ink diffuses, and the interweaving of warp and weft yarns makes the thickness of the prepared pattern uneven, resulting in large differences in FSS patterns, and the final pattern square resistance uniformity is poor, resulting in a decrease in absorbing performance.
[0088] Comparative Example 7
[0089] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0090] S2: The aramid fiber unidirectional fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities and colloids on the surface of the aramid fiber unidirectional fabric are completely removed; the desired FSS pattern is prepared on the treated aramid fiber unidirectional fabric using PEDOT:PSS conductive ink by screen printing;
[0091] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, lay 5 layers of aramid fiber plain weave / epoxy resin prepreg on the middle layer, and lay a layer of epoxy resin film, a layer of aramid fiber unidirectional cloth, a layer of epoxy resin film, a layer of aramid fiber unidirectional cloth printed with FSS pattern and a layer of epoxy resin film on the top layer from bottom to top. The schematic diagram of the laying is shown in the figure. Fig.12 As shown; put it into the mold after leveling; place the mold in a hot press, evacuate, heat and pressurize, keep warm and pressurize, and finally cool it; hot press it at 150°C and 8MPa for 25min, cool it naturally to below 50°C, demold it and take it out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0092] In comparative example 7, the FSS pattern substrate is aramid fiber unidirectional cloth, the dielectric layer is aramid fiber plain weave / epoxy resin prepreg, and the top layer has an epoxy resin protective layer. Through testing, the density of the absorbing composite material is 1.114g / cm 3 , thickness 3.2mm, FSS film square resistance cond = 30 ± 8Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2 to 18GHz is 10.24GHz (7.76 to 18.00GHz), and tensile strength is 482.9MPa.
[0093] The present invention is applicable to the preparation of any metasurface absorbing composite material that requires a relatively fine FSS pattern, and can greatly improve the accuracy and square resistance uniformity of the FSS pattern. The square patch used in this study has a strong design, including five parameters: periodic unit side length P, square side length a, square patch square resistance cond, and dielectric layer thickness h1 and h. The top view and side view of the absorber containing the unit geometry are shown in FIG. Fig.15 The designed metamaterial absorber is simulated using the frequency domain solver of the electromagnetic simulation software CST Microwave Studio. The absorber is placed in the xy plane in a periodic distribution, and the z direction is set as an open (add space) boundary. The simulation frequency is 2 to 18 GHz.
[0094] In order to verify the accuracy of the model, a composite material containing FSS film with the corresponding parameters of the optimal absorbing performance was prepared, with the periodic unit side length P = 10mm, the patch side length a = 6mm, the patch square resistance cond = 50Ω / sq, the dielectric layer thickness h1 = 2.0mm, h = 3.4mm. The accuracy of the simulation was verified by comparing the experiment with the simulation. The square resistance of the FSS film was tested by the four-probe method, and the absorbing performance of the structural and functional integrated absorbing composite material containing the FSS film was tested by the bow method. Fig.16 The schematic diagram of the FSS periodic structure can be obtained.
[0095] Comparative Example 8
[0096] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0097] S2: The PI film is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that impurities on the surface of the PI film are completely removed; the desired FSS pattern is prepared on the treated PI film using PEDOT:PSS conductive ink by screen printing;
[0098] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, and lay 5 layers of aramid fiber plain weave / epoxy resin prepreg in the middle layer. Then, lay a layer of epoxy film, a layer of PI film printed with FSS pattern and a layer of epoxy film from bottom to top, and lay 3 layers of aramid fiber plain weave / epoxy resin prepreg on the top layer. The layup diagram is shown in the figure. Fig.17 As shown, after being leveled, it is placed in a mold; the mold is placed in a hot press, vacuumed, heated and pressurized, kept warm and pressed, and finally cooled; hot pressed at 150°C and 8MPa for 25 minutes, naturally cooled to below 50°C, demolded and taken out, to obtain a super-surface broadband absorbing composite material based on a new super-surface substrate material.
[0099] In Comparative Example 8, the FSS square pattern substrate is a PI film, and the dielectric layer is an aramid fiber plain weave / epoxy resin prepreg. Through testing, the density of the absorbing composite material is 1.201 g / cm 3, thickness 3.6mm, FSS film square resistance cond = 50 ± 5Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2 to 18GHz is 8.12GHz (8.21 to 16.33GHz), and tensile strength is 408.5MPa. However, due to the poor compatibility between PI film and epoxy resin, stratification occurs between the two, resulting in the collapse of the overall structure of the later absorbing composite material and a sharp decline in absorbing performance. Secondly, because the surface of the aramid fiber plain fabric is not flat enough, the surface of the PI film printed with the FSS pattern after hot pressing is printed with fabric texture, which affects the accuracy of the FSS pattern and causes a slight decline in absorbing performance.
[0100] Comparative Example 9
[0101] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0102] S2: The aramid fiber plain fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that the colloid and impurities on the surface of the aramid fiber plain fabric are completely removed; the desired FSS pattern is prepared on the treated aramid fiber plain fabric using PEDOT:PSS conductive ink by screen printing;
[0103] S3: Apply mold release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, and lay 5 layers of aramid fiber plain weave / epoxy resin prepreg in the middle layer. Then, lay a layer of epoxy film, a layer of aramid fiber plain weave fabric printed with FSS pattern and a layer of epoxy film from bottom to top, and lay 3 layers of aramid fiber plain weave / epoxy resin prepreg on the top layer. The layup diagram is shown in the figure. Fig.18 As shown; put it into the mold after leveling; place the mold in a hot press, evacuate, heat and pressurize, keep warm and pressurize, and finally cool it; hot press it at 150°C and 8MPa for 25min, cool it naturally to below 50°C, demold it and take it out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0104] In Comparative Example 9, the FSS square pattern substrate is aramid plain fabric, and the dielectric layer is aramid fiber plain weave / epoxy resin prepreg. Through testing, the density of the absorbing composite material is 1.244 g / cm 3, thickness 3.6mm, FSS film square resistance cond=50±40Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2~18GHz is 6.14GHz (8.12~14.26GHz), and tensile strength is 448.7MPa. Due to the capillary effect of aramid fiber, the conductive ink diffuses, and the interweaving of warp and weft yarns makes the thickness of the prepared pattern uneven, resulting in large differences in FSS patterns, and the final pattern square resistance uniformity is poor, resulting in a decrease in absorbing performance.
[0105] Comparative Example 10
[0106] S1: The preparation process of PEDOT:PSS conductive ink is the same as that of Example 1;
[0107] S2: The aramid fiber unidirectional fabric is placed in an acetone solution in an ultrasonic cleaner for 2 hours of shaking cleaning, and then placed in an oven at 80°C for 1 hour for drying for later use, to ensure that the colloid and impurities on the surface of the aramid fiber unidirectional fabric are completely removed; the desired FSS pattern is prepared on the treated aramid fiber unidirectional fabric using PEDOT:PSS conductive ink by screen printing;
[0108] S3: Apply release agent to the mold surface 2 to 3 times, with an interval of 5 minutes each time, and then cut the required materials into a mold size of 200mm×200mm. Lay 2 layers of carbon fiber unidirectional / epoxy resin prepreg in a horizontal and vertical cross-laying manner on the lower layer, and lay 5 layers of aramid fiber unidirectional / epoxy resin prepreg in the middle layer. Then, lay a layer of epoxy film, a layer of aramid fiber unidirectional cloth printed with FSS pattern and a layer of epoxy film from bottom to top, and lay 3 layers of aramid fiber unidirectional / epoxy resin prepreg on the top layer. The layup diagram is shown in the figure. Fig.19 As shown; put it into the mold after leveling; place the mold in a hot press, evacuate, heat and pressurize, keep warm and pressurize, and finally cool it; hot press it at 150°C and 8MPa for 25min, cool it naturally to below 50°C, demold it and take it out to obtain a super-surface broadband absorbing composite material based on the new super-surface substrate material.
[0109] In comparative example 10, the FSS square pattern substrate is aramid unidirectional cloth, and the dielectric layer is aramid fiber unidirectional / epoxy resin prepreg. Through testing, the density of the absorbing composite material is 1.208g / cm 3 , thickness 3.6mm, FSS film square resistance cond = 50 ± 8Ω / sq, EAB with reflection loss less than -10dB in the frequency range of 2 to 18GHz is 8.97GHz (8.55 to 17.52GHz), and tensile strength is 554.3MPa.
[0110] By using aramid unidirectional cloth as the substrate of the FSS pattern, the present invention successfully solves the problem that the traditional FSS substrate is not stretchable and cannot be applied to complex three-dimensional structures, while improving the preparation integrity of the FSS pattern and the control of the uniformity of the pattern square resistance. Compared with the PI film or woven fabric used in existing studies, this solution greatly improves the compatibility of the FSS substrate with the resin matrix, ensuring the uniformity and integrity of the pattern. In addition, by designing a dielectric protective layer on the surface of the FSS pattern, the problem of decreased absorption performance caused by wear damage or local delamination when the pattern is exposed to external conditions is effectively avoided. Combined with the electromagnetic simulation design of metamaterials, the absorbing composite material is finally significantly optimized in terms of "thin, light, wide, and strong" performance, showing higher reliability and durability in various application environments.
Claims
1. A method for preparing a supersurface broadband absorbing composite material based on a novel supersurface substrate material, characterized in that: The following steps are involved: S1: adding polymer beads to a PEDOT:PSS dispersion, standing, stirring, removing the beads, freeze-drying to obtain solid PEDOT:PSS, and mixing the solid PEDOT:PSS with a solvent to obtain a PEDOT:PSS conductive ink; S2: The aramid unidirectional fabric is vibrated and cleaned in acetone and dried; the PEDOT:PSS conductive ink obtained in S1 is used to prepare an FSS pattern on the treated aramid unidirectional fabric by screen printing, and then placed in an oven for drying to obtain an aramid unidirectional fabric printed with the FSS pattern; S3: Apply a release agent to the mold surface, cut the aramid fiber unidirectional / epoxy resin prepreg, aramid unidirectional cloth, aramid unidirectional cloth printed with FSS pattern, epoxy resin film and carbon fiber unidirectional / epoxy resin prepreg into the size of the mold, lay the carbon fiber unidirectional / epoxy resin prepreg, aramid fiber unidirectional / epoxy resin prepreg, epoxy resin film, aramid fiber unidirectional cloth printed with FSS pattern and epoxy film from bottom to top, perform hot pressing molding, naturally cool and demold, and obtain a metasurface broadband absorbing composite based on the new metasurface substrate material.
2. The method for preparing a super-surface broadband absorbing composite material based on a novel super-surface substrate material according to claim 1, characterized in that: The standing time described in S1 is 1 to 2 hours, the stirring interval time is 20 to 30 minutes, and the freeze-drying time is 72 hours.
3. The method for preparing a super-surface broadband absorbing composite material based on a novel super-surface substrate material according to claim 1, characterized in that: The shaking cleaning time described in S2 is 2 to 5 hours, the drying temperature is 80 to 100° C., and the time is 0.5 to 1 hour.
4. The method for preparing a super-surface broadband absorbing composite material based on a novel super-surface substrate material according to claim 1, characterized in that: The carbon fiber unidirectional / epoxy resin prepreg described in S3 has 1 to 3 layers.
5. The method for preparing a super-surface broadband absorbing composite material based on a novel super-surface substrate material according to claim 1, characterized in that: The size of the mold in S3 is 200 mm×200 mm.
6. The method for preparing a super-surface broadband absorbing composite material based on a novel super-surface substrate material according to claim 1, characterized in that: The hot pressing process described in S3 is performed at a temperature of 150° C., a pressure of 8 MPa, and a time of 25 min.
7. A super-surface broadband absorbing composite material based on a novel super-surface substrate material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The metasurface broadband absorbing composite material based on the novel metasurface substrate material has a layered structure in which two layers of carbon fiber unidirectional / epoxy resin prepreg are laid in a horizontal and vertical cross-laying manner on the lower layer, six layers of aramid fiber unidirectional / epoxy resin prepreg are laid in the middle layer, and a layer of epoxy film, a layer of aramid fiber unidirectional cloth printed with an FSS pattern, and a layer of epoxy film are laid in sequence on the top layer from bottom to top.
Citation Information
Patent Citations
Aramid fiber / aluminum alloy composite material as well as preparation method and application thereof
CN106739364A
Resistive film frequency selective surface composite wave absorber and preparation method thereof
CN113555694A
Foam electromagnetic shielding material with bulletproof function and preparation method thereof
CN115651325A
Interlayer antenna housing structure
CN221828144U
Wave-absorbing composite material and preparation method therefor
WO2022267289A1